The integration of CFD and VR methods to assist auxiliary ventilation practice - Silvester, Stephen (2002)
The current trend towards the adoption of retreat longwall mining methods and the associated rapid development of the access drivages has exacerbated the environmental conditions experienced within these workings. The combined use of roof bolt and continuous miner systems has improved the face advance rate within rapid development drivages. In order to maintain adequate dust and gas control it is essential that the auxiliary ventilation and monitoring systems are correctly installed and maintained.